Viral vector vaccines make memory T cells against malaria. - Reyes-Sandoval, A; Harty, J; Todryk, S (2007)
Vaccines that comprise attenuated viral vectors encoding antigens from target pathogens generate potent T-cell responses. One such pathogen is malaria, and in particular the liver stage of its life cycle. Immunogenicity and efficacy studies in animals and humans have revealed the generation of memory T cells of both the central and effector phenotypes, depending on the viral vectors used in the malaria vaccination regime (viral species and serotype, combination and sequence for prime-boost) and suggest a divergence in their protective role. Being able to influence the memory T-cell make-up in a rational manner may allow us to develop more efficacious vaccines.